Comparison of Breastfeeding and Exclusive Formula Feeding Rates 2-3 and 6-8 Weeks After Delivery Amongst Primiparas [21E]. Issue 5 (May 2017) - Batig, Alison; Carty, Jenava
Abstract : INTRODUCTION: Our study's objective was to compare breastfeeding and exclusive formula feeding rates amongst primiparous women with an expressed intent to breastfeed during their admission for childbirth when randomized to either a 2-3 or 6-8 week follow up interval. METHODS: The data for this study was obtained as part of a randomized controlled trial that recruited term, primiparous women with an expressed intent to breastfeed to postpartum appointment intervals of either 2-3 or 6-8 weeks following childbirth. At the time of their postpartum encounter, their infant feeding method was categorized and compared using an odds ration with 95% CI. RESULTS: Of the 340 women enrolled in the study, 307 returned for a postpartum appointment where their infant feeding could be assessed. For 4 women in each group, infant feeding status was not denoted in their encounter record. Women randomized to the 2-3 week follow up interval were less likely to report exclusive formula feeding (OR 0.16, 95% CI 0.05-0.46, p < 0.01) and more likely to report breastfeeding of any degree (OR 6.41, 95% CI 2.15-19.11, p < 0.01). CONCLUSION: Amongst primiparous women with an expressed intent to breastfeed during their inpatient postpartum stay, our study demonstrated that women seen for earlier postpartum follow up were more likely to report breastfeeding to any degree and less likely to report exclusive formula feeding. Our findings suggest significant breastfeeding attrition may occur between 2-3 and 6-8 weeks after delivery. Understanding the timing for breastfeeding attrition may help us to target interventions to promote breastfeeding success and continuation.